Primordial black holes as dark matter candidates: multi-frequency constraints from cosmic radiation backgrounds - Casanueva Villarreal, Catalina Isabel; Padilla, N.; Tissera, P. B.; Liu, Boyuan; Bromm, V. (Astronomy and astrophysics, 2025)
Aims. This study investigates the role of primordial black holes (PBHs) in shaping cosmic radiation backgrounds, specifically the cosmic X-ray background (CXB), the Lyman-Werner background (LWB), and the cosmic radio background (CRB). It assesses their viability as dark matter (DM) candidates based on both observational constraints and theoretical limits. Methods. PBH accretion is modelled using analytical frameworks, including electron advection-dominated accretion flows (eADAF), standard ADAF, luminous hot accretion flows (LHAF), and thin discs. Contributions to the CXB, LWB, and CRB are calculated for PBHs in both halos and the intergalactic medium (IGM). To test robustness, we explore variations in the model, such as halo density profiles, gas velocities and emission models. The results are compared against observational limits and theoretical thresholds across these backgrounds, constraining the PBH fraction as DM for masses between 1 and 100 M⊙. Results. Our findings suggest that PBHs can contribute up to 99, 93, 80, and 91 per cent of the observed non-source soft X-ray background for masses of 1 M⊙, 10 M⊙, 33 M⊙, and 100 M⊙, respectively, while contributing approximately 33, 37, 33, and 39 per cent to the hard X-ray background. These contributions constrain the maximum DM fraction in the form of PBHs to 7 × 10 −3, 6 × 10 −4, 6 × 10 −4, and 7 × 10 −4 for the respective masses under the baseline model. These constraints align with the limits imposed by the LWB, ensuring that PBHs do not disrupt molecular cooling or early star formation under these conditions. However, explaining the observed radio background excess at z= 0 and the EDGES signal would require DM fractions composed of PBHs significantly larger than those allowed by these constraints. For 1 M⊙, excluding subregimes in the ADAF framework relaxes the constraint to 3 × 10 −2, highlighting the impact of the modelled accretion physics on the derived limits. Variations in model assumptions, such as halo density profiles, gas velocities, emission models, and modifications to the halo mass function, introduce slight changes in the predicted backgrounds.
Online veröffentlicht: 27. Juni 2025
Gesehen am 31.10.2025